Improved Quasi-Z-Source Inverter Based on Switching Inductor - Fang, Xupeng; Zhang, Xinyu; Wang, Jian; Meng, Xiangrui (2025 2nd International Conference on Electrical Technology and Automation Engineering (ETAE), 2025)
In order to solve the shortcomings of the traditional quasi-Z-source inverter (qZSI), such as limited boost capability, high voltage stress, and poor output waveform quality, this paper proposes an improved quasi-Z-source inverter based on switched inductors (ISI-qZSI). Through the detailed analysis of its working principle and main performance parameters, alongside the comparison with the quasi-Z-source inverter topology before the improvement, it is verified that the new quasi-Z-source inverter has significantly improved boosting capability and can obtain high boosting capability at a low duty cycle, which broadens the modulation range. It also has the characteristics of low voltage stress and low inductor current ripple. Finally, a simulation verification and an experimental prototype are carried out to demonstrate the superiority and reliability of the ISI-qZSI.